PHYSICOCHEMICAL METHODS FOR NEUTRALIZING ACID MINE DRAINAGE IN COAL MINING AREAS - Urozova Durdonakhon Davronjon qizi (Western European Studies, 2025)
Acid mine drainage (AMD) is one of the most severe environmental consequences of coal mining, characterized by the outflow of acidic water rich in heavy metals and sulfates. Its generation poses long-term ecological and public health threats due to soil and water contamination. This study reviews and evaluates various physicochemical methods—such as lime neutralization, active/passive treatment systems, ion-exchange resins, and adsorption using industrial by-products—for the effective neutralization and removal of acidity and metal ions from AMD. Laboratory-based tests and field data were analyzed to assess treatment efficiency, operational cost, and environmental impact. The findings indicate that integrated physicochemical approaches offer a promising solution for AMD management, especially when tailored to site-specific conditions. Recommendations for sustainable implementation in post-mining land restoration strategies are also presented.
Keywords: Acid mine drainage; coal mining; neutralization